THE TECTONIC SETTING OF THE OCTOBER 8 m 2005 EARTHQUAKE IN KASHMIR, NORTH PAKISTAN - Skourtsos, E.; Lekkas, E. (Bulletin of the Geological Society of Greece, 2007)
On the 8th of October 2005 an earthquake of magnitude 7.6 occurred in northern Pakistan. The earthquake epicenter was located in Pakistan Kashmir, 90 km north of Islamabad, the capital of Pakistan. The focal depth was 26 km triggered by a thrust fault striking NW-SE and of 40o dip angle towards the NE. The mean fault slip was estimated as 4 m. The aftershocks epicenters were located northeastwards of the Indus - Kohistan Seismic Zone. The structures that trace the activated fault were distributed along the southwestern limb of the Muzaffarabad anticline and grouped as structures of flexural-slip folding, structures that are correlated to folding and normal faults. The latter may represent overturned segments of the seismic fault on the high-angle limb of the Muzaffarrabad anticline. This anticline is located on the hanging wall of a thrust fault with geometry and kinematics characteristics similar to those of the Indus — Kohistan Seismic Zone. This zone, from the Hazara - Kashmir Syntaxis to the Swat River represents a blind thrust under the metamorphosed rocks of the Lower Himalayas, while in the region of Sub- Himalayas becomes a distinct structure. This thrust fault is linked in depth to the Main Himalaya Thrust through which, the cratonic basement of India is subducting under its sedimentary cover.